2022
DOI: 10.13080/z-a.2022.109.047
|View full text |Cite
|
Sign up to set email alerts
|

Sodium nitroprusside and acetylsalicylic acid provided earliness in peach flower bud phenological stages by triggering xylogenesis

Abstract: Temperate trees are subjected to a quiescent state during autumn and winter called dormancy. During buds growth, xylogenesis was observed between buds and shoots to maintain water and nutrients. In the present study, the effect of sodium nitroprusside (SNP) and acetylsalicylic acid (ASA) on peach (Prunus persica (L.) Batsch, 'J. H. Hale') flower bud phenological stages and xylogenesis between buds and shoots was investigated. Shoots were collected during the leaf fall from peach trees grafted onto the Garnem r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The NO triggers xylem formation through programmed cell death (Yu et al, 2014). Some studies showed that NO is involved in xylem formation in buds and xylem improvement in leaves (Aras, 2022b;2022c). In the current study we examined xylem conduit diameter of leaf midrib.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The NO triggers xylem formation through programmed cell death (Yu et al, 2014). Some studies showed that NO is involved in xylem formation in buds and xylem improvement in leaves (Aras, 2022b;2022c). In the current study we examined xylem conduit diameter of leaf midrib.…”
Section: Discussionmentioning
confidence: 94%
“…Studies have been conducted in many plant species to determine the effectiveness of SNP under salt stress (Khoshbakht et al, 2018;Shams et al, 2019;Jabeen et al, 2021). Moreover, SNP provided early xylem formation in peach bud (Aras, 2022c) and xylem improvement (Aras, 2022b).…”
Section: Introductionmentioning
confidence: 99%